Switchable bandstop to allpass filter using cascaded transmission line SIW resonators in K-band - Amirul Aizat Zolkefli; Noor Azwan Shairi; Badrul Hisham Ahmad; Adib Othman; Nurulhalim Hassim; Zahriladha Zakaria; Imran Mohd Ibrahim; Huda A. Majid (Institute of Advanced Engineering and Science, 2021)
In this paper, a switchable bandstop to allpass filter using cascaded transmission line SIW resonators is proposed. The switchable filter is performed by the switchable cascaded transmission line SIW resonators using discrete PIN diodes. Therefore, it can be used for rejecting any unwanted frequencies in the communication systems. The proposed filter design is operated in K-band and targeted for millimeter wave front end system for 5G telecommunication. Two filter designs with different orientation (design A and B) are investigated for the best performance and compact size. As a result, design B is the best by giving a maximum attenuation of 39.5 dB at 26.4 GHz with the layout size of 33×30 mm.